AWS development fundamentals (LiveLessons (Indianapolis, Ind.), 2017)
This video presents an overview of the Amazon Web Services (AWS) and cloud computing. After viewing the video the user should have a firm understanding of: compute instances in AWS, virtual private cloud concepts and deployment, database options, identity and authentication, security constructs, and AWS API.--From video "Success Criteria" screen